7C.10: PROTHROMBOTIC MARKERS ARE RELATED TO CAROTID STIFFNESS IN ESSENTIAL HYPERTENSIVE PATIENTS. (June 2015) - Catena, C.; Colussi, G.L.; Frangipane, A.; Clinaz, L.; Sechi, L.A.
Abstract : Objective: A prothrombotic state is associated with presence and severity of organ damage in hypertensive patients. In these patients, evidence of subclinical carotid damage anticipates major cardiovascular events. The aim of this study was to investigate the association of prothrombotic markers with carotid stiffness in hypertension. Design and method: In 116 hypertensive patients (age 49 ± 13 years; 54 males) we assessed common carotid artery stiffness by B-mode ultrasonography and measured plasma fibrinogen, D-dimer, plasminogen-activator inhibitor-1 (PAI-1), homocysteine, lipoprotein(a), and C-reactive protein. Results: No significant differences were observed in fibrinogen, D-dimer, lipoprotein(a), homocysteine, and C-reactive protein levels between patients with values below or above the median of the distribution of carotid distensibility, compliance, coefficient of distensibility, coefficient of compliance, Young elastic modulus, and beta-stiffness. Only PAI-1 levels were borderline higher in patients with high values of the Young elastic modulus than in patients with low values (P = 0.042). The Young elastic modulus was significantly correlated with age and PAI-1 levels (r = 0.286, P = 0.036), whereas no further significant correlation between non-traditional cardiovascular risk factors and indices of carotid stiffness was observed. Stepwise multivariate regression analysis indicated that Young elastic modulus was independently associated with age and PAI-1 (B = 0.289, P = 0.028). Conclusions: The findings of this study do not support the involvement of a prothrombotic state and other non-traditional cardiovascular risk factors related to the hemostatic system in carotid artery stiffening of hypertensive patients.